Sosialisasi Etika Digital sebagai Upaya Meningkatkan Civic Skill Mahasiswa Dalam Menghadapi Tantangan Digital - Melisa, Melisa; Utami, Sundari; Tiara Maulia, Siti (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2023)
In an increasingly advanced digital era, the use of information and communication technology has become an inseparable part of everyday life, especially the internet. In this case, the internet functions as a two-sided sword that can provide good benefits, but can also provide bad benefits. Students as a digital native generation who grow and develop in the midst of this technological development, face various problems in managing and utilizing technology wisely. To be able to overcome these problems, the socialization team conducted socialization activities on digital ethics as an effort to improve student civic skills in facing digital challenges. The purpose of this service activity is to increase understanding of digital ethics for students. The number of socialization participants was 30 students. From the results of these activities, a post-test evaluation was carried out using a multiple choice questionnaire via google form. The questions are written in the form of essays consisting of two answers Yes or No. The results of the google form questionnaire showed that 90% of students understood the digital ethics socialization material. Thus, it can be concluded that the socialization of digital ethics helps students improve the civic skills needed to face digital challenges. Â